Literature Review: Development of Student Worksheets (LKPD) Integrated Socio-Scientific Issues (SSI) - Kirana, Sella Jamatul; Arsih, Fitri (Biosel Biology Science and Education, 2024)
Preparing the current generation for education is very important. Implementation of the learning process is a way to achieve educational goals. Learning media can support the learning process and function as well as possible. Student Worksheets are one type of effective learning resource (LKPD). Designing LKPD with social and scientific issues (Socio-Scientific Issues) integrated into it is one way to inspire students to actively seek solutions to the challenges they face. LKPD produced with an emphasis on problem solving is LKPD that can be used in learning. When LKPD is combined with social studies topics, students become more involved, independent and cooperative, thereby helping them solve problems and sharpen their critical thinking skills. Through a study of various journal papers that are related to each other and published between 2018 and 2024, this research uses descriptive research in the form of literature review. Referenced papers are published in Indonesian and English and can be found in a number of media databases, including Google Scholar and Science Direct. SSI's integrated LKPD has an impact on the teaching and learning process, according to the findings of the article review, because it helps students become aware of the dangers of the environment around them. Considering that the Integrated Socio-Scientific Issues (SSI) LKPD can improve students' critical thinking, it can be said to be suitable for use in the classroom.  Keywords: Student Worksheet, Literature Review, Socio-Scientific Issue